211k views
3 votes
Solve x + 3y = 9 3x − 3y = −13

User Chinelle
by
5.5k points

2 Answers

3 votes

Answer:

The solution is (-1,10/3).

Explanation:

We have given a system of equations.

x + 3y = 9 eq(1)

3x − 3y = −13 eq(2)

We have to find the solution of given system.

From eq(1),

x = 9-3y eq(3)

Putting the value of x in eq(2), we have

3(9-3y)-3y = -13

27-9y-3y = -13

27-12y = -13

Adding -27 to both sides of above equation, we have

-27+27-12y = -27-13

-12y = -40

y = -40 / -12

y = 10/3

Putting the value of y in eq(3), we have

x = 9-3(10/3)

x = 9-10

x = -1

hence, the solution is (-1,10/3).

User Eyal
by
5.2k points
6 votes

Answer:

x=-1

y=10/3

Explanation:

You can solve the system of equations by applying the elimination method as following:

- Add both equations, then:


x+3y=9\\3x-3y=-13\\-------\\4x=-4\\x=-1

- Finally, you must substitute the value of x obtained into one the original equations and then you must solve fot y:


x+3y=9\\-1+3y=9\\3y=10\\y=10/3

User AlanObject
by
5.3k points